Change And Evolution Of Mihrab Motifs - Azizi, Sara (The Turkish Online Journal of Design Art and Communication, 2016)
In this study, at first we tried to provide the meaning and concept of the Mihrab in dictionaries and also its place in mystical literature. In the next stage, different classifications and theories about the origins of the Mihrab and the origin of this design was examined and in any case the necessary explanations were provided; For example, on the Mihrab in Islam after stating the theory, topics such as the initial altars, altar design in the mosques, the Muslim world's most famous altars, altar in Islamic architecture and … are mentioned; Or on the theory of Mihrab and Mehrabeh after explaining the relationship between the Mihrab with Mehrabeh in Mehri religion, about the form of Mehrabeh, allegory of killing cattle, Iran's Mehrabeh have been discussed. After investigating the relationship between Iranian nomadic saltshakers with the Mihrab design, various Mihrab designs with photos of it were described, and in the end, in addition to reviewing the symbol of Mihrab and prayer rug carpets, some examples of Mihrab carpets in the carpet museum were investigated.
Keywords: Mihrab; Mehrab; Mehri religion; Mithraist Regulation; evolution of designs; prayer rug designs; Mihrap; Mehrab tasarımlar; seccade tasarımları; Mehri din; Mithraici Yönetmeliği